Counsellorsâ Knowledge And Use Of Anecdotal Records In Secondary Schools Guidance Services: Implication For Counselling - Banke Iyabo, Omoniyi, Mary (Social Science Learning Education Journal, 2017)
Appraisal services involve gathering, organising, and interpreting information or data about the student for the purpose of understanding himself and his world. Information about the student is usually collected through psychological tests and written reports. The study was carried out to find out the school counsellorsâ knowledge and use of anecdotal records â a non âtest technique as a means of gathering information about students. The sample consists of 98 guidance counsellors randomly selected from the state secondary schools in Ondo State, Nigeria. A self-constructed 15 item questionnaire with a reliability coefficient of r= 0.94 was employed to elicit information from respondents. The result showed that majority of the counsellors 96(97.95%) have read about anecdotal forms. However all the counsellors sampled did not use them during their training as counsellors and have never made use of them as trained counsellors. Though they are aware of other assessment tests but the tests are not available in schools 66 (67.35%), Moreover only 40 (40.82%) of the counsellors can interpret these other tests adequately. The result also showed a significant relationship between counsellorsâknowledge of anecdotal record forms and access to them. There is also significant correlation between counsellorsâ knowledge of anecdotal forms and their use.However there is no significant correlation between counsellorsâ knowledge of other forms of assessment and the interpretation of anecdotal record forms..Counselling implications were therefore highlighted for holistic and efficient schools guidance services.